The Lao People's Democratic Republic : Systemic Transformation and Adjustment - Otani, Ichiro (Occasional Papers; Occasional Paper, 1996)
Faced with a steadily worsening economy, the government of the Lao Peoples Democratic Republic took its first steps toward reforming its centrally planned economy in December 1979. The reform process gathered momentum with the introduction of the New Economic Mechanism in 1985, as the authorities began a series of far-reaching policy reforms in virtually all economic areas. This paper provides a much-needed overview of the Lao P.D.R.'s experience with systemic transformation and macroeconomic adjustments in recent years and highlights challenges that the country is likely to face in the coming years.